2001
DOI: 10.1111/j.1600-0528.2001.290508.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative anti‐caries efficacy of 1100, 1700, 2200, and 2800 ppm fluoride ion in a sodium fluoride dentifrice over 1 year

Abstract: – There is limited evidence from clinical trials on the dose response of sodium fluoride dentifrices at concentrations above 1100 ppm fluoride ion, with respect to caries efficacy. This randomized, double‐blind study examined the anti‐caries effectiveness of sodium fluoride dentifrices containing 1700 ppm, 2200 ppm and 2800 ppm fluoride ion relative to an 1100 ppm fluoride ion control. A population of 5439 elementary schoolchildren, aged 6–15 years, was recruited from an urban central Ohio area with a low fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…These are not recommended for children. The benefits of 2,800 ppm have been demonstrated in various clinical trials [27,37,38], and the additional caries-preventive effect has to be estimated at around 15% (table 1) [25]. Nordström and Birkhed [39] showed that volunteers aged 14-16 years with DMFS ≥5 using 5,000-ppm F toothpaste had significantly lower caries progression compared to those using 1,450-ppm F toothpaste with a prevented fraction of 40%, with those with poorer compliance showing a slightly higher prevented fraction (42%).…”
Section: Desirable Concentrationmentioning
confidence: 99%
“…These are not recommended for children. The benefits of 2,800 ppm have been demonstrated in various clinical trials [27,37,38], and the additional caries-preventive effect has to be estimated at around 15% (table 1) [25]. Nordström and Birkhed [39] showed that volunteers aged 14-16 years with DMFS ≥5 using 5,000-ppm F toothpaste had significantly lower caries progression compared to those using 1,450-ppm F toothpaste with a prevented fraction of 40%, with those with poorer compliance showing a slightly higher prevented fraction (42%).…”
Section: Desirable Concentrationmentioning
confidence: 99%
“…Fluoride-containing dentifrices and mouthrinses have been demonstrated to decrease caries experience in randomized, controlled clinical trials. 1,2 Fluoride ions promote the formation of fluorapatite or fluorhydroxyapatite in the presence of calcium and phosphate ions and this is now believed to be the major mechanism of fluoride's action. 3,4 The intrinsic sources of calcium and phosphate are from saliva, dissolved tooth structure and to a lesser degree, gingival crevicular fluid.…”
Section: Introductionmentioning
confidence: 99%